Cancer in Central and South America: Methodology. (September 2016) - Sierra, Mónica S.; Forman, David
Highlights: 60% (53/88) cancer registries responded to the data call to participate in this project. 41% (22/53) of the registries had been accepted in Cancer Incidence in Five Continents Vol X. The quality of the incidence data from some registries is suboptimal. 60–97% of all cancer cases combined (except non-melanoma skin cancer) were MV in most registries. 0–45% of all cancer cases combined were DCO; 11 registries recorded <2% DCO cases. Abstract: Statistics on cancer incidence from Central and South American countries are scarce because of the small number of population-based cancer registries that continuously collect data. Similarly, comparable statistics on cancer mortality are sparse in spite of efforts made to improve coverage in the last decade. The aim of this study is to describe geographical patterns and trends in cancer incidence and mortality in Central and South America in the 21st century. The primary objective was to obtain the best quality cancer data available from each country within the region. Cancer incidence data were obtained from population-based cancer registries within the region and, in countries where these did not exist, from hospital-based registries; national mortality data were obtained from the World Health Organization mortality database. Given the variability in data quality – mainly due to the age and development in maturity of the registries, an exhaustive review of the data was necessary in order to appropriately analyze, describe and interpret patterns of cancer incidence and mortality between countries and within cancer-specific sites. This paper presents the methods employed in the collection, quality control and analysis of the datasets received for the project.